HUBUNGAN ANTARA GENDER DENGAN KEMAMPUAN MEMECAHKAN MASALAH - Yogi Fitriani; Tri Jalmo; Berti Yolida (Universitas Lampung, 2015)
The aims of this research were to figure out the correlation between gender and problem solving skill and the differences between male students' and female students' skill in problem solving. The design of research was correlation descriptive by using cluster random sampling technique, with 33 male students and 34 female students in grade X SMA Negeri 1 Pringsewu as sample of this research. The research data were a quantitative data which was obtained from problem solving skill test result and a qualitative that was result of problem solving description, engagement, and students' response and also the observation of students' activity. The research result showed that there was low correlation between gender and provlem solving skill and male students got higher significantly score (76,10) than female students (60,32). Therefore, it can be concluded that there is difference between male students' and female students' in problem solving.Tujuan penelitian ini untuk mengetahui hubungan antara gender dengan kemampuan memecahkan masalah dan perbedaan kemampuan pemecahan masalah siswa laki-laki dan perempuan. Desain penelitian adalah deskriptif korelasi dengan teknik pengambilan sampel cluster random sampling, sebanyak 33 orang siswa laki-laki dan 34 orang siswa perempuan kelas X SMA Negeri 1 Pringsewu. Data penelitain berupa data kuantitatif yang diperoleh dari hasil tes kemampuan pemecahan masalah dan data kualitatif yang diperoleh dari deskripsi kemampuan pemecahan masalah, keterlibatan, dan tanggapan siswa serta observasi aktivitas siswa. Hasil penelitian menunjukkan bahwa terdapat hubungan dengan tingkat korelasi yang rendah antara gender dengan kemampuan memecahkan masalah dan siswa laki-laki mendapat skor lebih tinggi (76,10) secara signifikan daripada siswa perempuan (60,32). Dengan demikian, dapat disimpulkan bahwa terdapat perbedaan antara kemampuan siswa laki-laki dan perempuan dalam memecahkan masalah.Kata kunci : gender, kemampuan, memecahkan masalah